Safety and efficacy of anti-CD30 CAR-T cell therapy in relapsed/refractory classic Hodgkin lymphoma: a systematic review and meta-analysis - Fanqiao Meng; Maoyuan Xiang; Yu Liu; Dongfeng Zeng (BMC Cancer)
Abstract Background Relapsed/refractory classic Hodgkin lymphoma (R/R cHL) remains challenging to treat, and anti-CD30 chimeric antigen receptor T (CAR-T) cell therapy may be effective. This meta-analysis investigates the efficacy and safety of anti-CD30 CAR-T cell therapy for treating R/R cHL. Methods A systematic literature search of PubMed, Cochrane, Embase, ClinicalTrials.gov, and Web of Science databases was conducted until February 2024. The odds ratio (OR) with a 95% confidence interval (CI) was analysed using Review Manager 5.4. Outcomes including overall response rate (ORR), complete response (CR), partial response (PR), progression-free survival (PFS), overall survival (OS), and adverse events (AEs) were extracted for meta-analysis. We used the Methodological Index for Non-Randomized Studies (MINORS) to evaluate the quality of the included literature. Results A total of 151 participants from 8 records were included. Meta-analysis showed the ORR of CD30 CAR-T cell therapy for R/R cHL was 57% (95%CI 0.36–0.76, P = 0.50), with a CR of 34% (95%CI 0.13–0.64, P = 0.29) and a PR of 32% (95%CI 0.15–0.55, P = 0.12). With the median follow-up range from 9.5 to 71.5 months, the 1-year PFS was 39% (95% CI 0.30–0.49, P = 0.04), and the 1-year OS was 89% (95% CI 0.65–0.97, P = 0.005). The most common hematologic AE was leukopenia (72%, 95% CI: 0.50–0.87), and the most common non-hematological AE was cytokine release syndrome (CRS) (43%, 95% CI: 0.14–0.76). The grade ≥ 3 AEs was 66% (95%CI 0.06–0.98, I2 = 93%, P = 0.70), 34% (95%CI 0.07–0.78, I2 = 85%, P = 0.51) in neutropenia and thrombocytopenia, respectively. All AEs were tolerable and resolved with treatment. Conclusion Current evidence suggests that anti-CD30 CAR-T cell therapy is effective and safe in treating R/R cHL and is worth considering as a viable therapeutic option.